THE MEASUREMENTS OF BALANCED SCORECARD TO SUPPORT PLANNING AND MANAGEMENT PERFORMANCE IMPROVEMENT AT UB GUEST HOUSE MALANG - Pongsapan, Marchelyn (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
Perforance measurement is a measurement used to help improve a company's management performance. In 2014 - 2015 UB Guest House experienced a decrease in management performance therefore this study aims to measure the performance of UB Guest House as a whole not only in terms of financial but in terms of non-financial so it can be used as a benchmark in planning and improving activityy in UB Guest House Malang continuously. This research is quantitative descriptive research and uses field research or observation techniques to collect data.The primary data is in the form of questionnaire and explained by Balamced Scorecard (BSC). From the analysis result using four perspectives in Balanced Scorecard, it showed that overall UB Guest House performs well and has a balance performance.Keywords: Balanced Scorecard, Financial Perspective, Customer Perspective, Internal Business Perspective, Growth Perspective and Learning.